Association of aortic root calcification severity with the extent of coronary artery calcification assessed by calcium-scoring dual-source computed tomography. Issue 10 (October 2015) - Hu, Xiaohan; Frellesen, Claudia; Kerl, J.Matthias; Bauer, Ralf W.; Beeres, Martin; Bodelle, Boris; Lehnert, Thomas; Vogl, Thomas J.; Wichmann, Julian L.
Highlights: Aortic root calcification (ARC) on calcium-scoring dual-source CT scans was assessed. Correlation with coronary artery calcification (CAC) using the Agatston score was analyzed. Patients with ARC showed a significantly higher presence of CAC. Patients with an ARC volume > 40 mm ≥ demonstrated significantly higher rates of severe CAC. The extent of ARC is directly associated with the presence and degree of CAC. Abstract: Purpose: To investigate the association between aortic root calcification (ARC) and coronary artery calcification (CAC) assessed by coronary artery calcium-scoring dual-source computed tomography (DSCT). Materials and methods: We retrospectively analyzed 143 consecutive patients who underwent coronary artery calcium-scoring during coronary DSCT angiography. 57 patients had findings of ARC on calcium-scoring scans. ARC volume (ARCV) and Agatston coronary artery calcium score (CACS) were calculated. Chi-square test was used to assess differences of categorical variables between patients with and without ARC. Statistical significances between both groups were assessed with the independent-Sample t test. Results: Compared with patients without ARC ( n = 86), patients with ARC ( n = 57) showed a significantly higher presence of CAC (87.7% vs. 24.4%; P < 0.001), and a higher mean CACS (700.6 ± 941.2 vs. 256.4 ± 724.3; P = 0.009) in patients with CAC. Patients with a calculated ARCV >40 mm 3 ( n = 32) showed significantly higher rates of severe CAC (56.3% vs. 24.0%; P = 0.014) compared with patients with an ARCV < 40 mm 3 ( n = 25). Compared with patients without CAC ( n = 42), patients with CAC ( n = 101) showed a significantly higher presence of ARC (83.3% vs. 50.5%; P < 0.001) and a higher mean ARCV (95.4 ± 116.2 mm 3 vs. 29.7 ± 33.0 mm 3 ; P = 0.003). Severe CAC ( n = 24) correlated with an increased mean ARCV (122.3 ± 148.8 mm 3 ) compared to patients with minimal to moderate CAC ( n = 33, mean ARCV: 61.9 ± 64.8 mm 3 ; P < 0.05). Conclusions: The extent of ARC is directly associated with the presence and degree of CAC on calcium-scoring scans during coronary DSCT angiography.